Ethnobotany in Morocco from 1990 to 2023: Part II- Analysis of Floristic Diversity, Conservation Status and treated diseases - Bemanar, Khadija; Benelfakir, Kawtar; Benamar, Saad (Ethnobotany Research and Applications, 2026)
Background: The medicinal and aromatic plants (MAPs) have been used in Moroccan traditional medicine. This review aims to make a synthesis of floristic data from ethnobotanical studies conducted between 1990 and 2023, in order to highlight plant diversity, use pattern, and conservation status. Methods: A total of 1427 plant species were cited across 230 ethnobotanical studies. The relative frequency of citation (RFC) index was calculated as an indicator of cultural importance. Phylogenetic relationships between the species that were commonly reported to possess antidiabetic potential were generated by MEGA X software through the Neighbor-Joining method. The IUCN status of the plants and native origin of plants were also assessed. Results: The most frequently cited botanical families were Lamiaceae, Asteraceae, Apiaceae, Fabaceae and Rosaceae, whereas Marrubium vulgare L., Mentha pulegium L., Rosmarinus officinalis L., Artemisia herba-alba Asso and Olea europaea L., were the most cited species. Native plants represented 65.53% of reported species, largely characterized as Least Concern (42.89%). The commonest treated diseases were diabetes, bronchopulmonary, and gastrointestinal diseases. Phylogenetic analysis revealed clustering of key antidiabetic species, suggesting potential links between evolutionary relationships and therapeutic properties. Conclusions: The ethnobotanical knowledge in Morocco is floristically rich, culturally varied and therapeutically important. The identification of most cited species and their conservation status can provide a reference for sustainable use, drug discovery, and traditional knowledge preservation. Keywords: Ethnobotanical review; medicinal plants; Morocco; plant citation index; phylogenetic analysis; IUCN conservation.